Melanin-concentrating hormone attenuates the hedonic feeding induced by orexin-A in the ventral tegmental area of high-fat diet male mice - Liu, Xiaoning; Yang, Helin; Xu, Wenguang; Wang, Xuezhe; Tang, Wenhui; Wang, Xiaoxuan; Jiao, Yang; Luan, Xinchi; Li, Pengmeng; Guo, Feifei (Frontiers in Nutrition, 2024)
ObjectiveThe ventral tegmental area (VTA), a pivotal hub in the brain’s reward circuitry, receives inputs from the lateral hypothalamic area (LHA). However, it remains unclear whether melanin-concentrating hormone (MCH) and orexin-A (OX-A) neurons in the LHA exert individual or cooperative influence on palatable food consumption in the VTA. This study aims to investigate the modulatory role of MCH and OX-A in hedonic feeding within the VTA of high-fat diet (HFD) mice.MethodsMale mice were subjected to an 8-week high-fat diet. To visualize the projections from the LHA to VTA, we employed fluorescent gold retrograde tracing combined with immunofluorescence staining. Immunofluorescence staining or enzyme-linked immunosorbent assay was used to detect the activity of the VTA neurons, expression of OX-A or MCH in the LHA, as well as the activity of their receptors (OXR1 and MCHR1) in the VTA following a sucrose preference test. Single-unit extracellular electrical discharge recordings were conducted to assess the effects of OX-A and MCH on VTA neurons in HFD mice. Additionally, chemogenetic inhibition of MCH neurons and immunofluorescence staining were utilized to observe the regulatory roles of MCH in changes of hedonic feeding induced by OX-A in HFD mice.ResultsSucrose intake resulted in lower activation of VTA neurons in the HFD mice compared to CON mice, while OX-Aergic and MCHergic neurons project from the LHA to the VTA. Although sucrose intake increased the expression of OX-A and MCH in HFD mice, it led to diminished activation of OXR1-positive and MCHR1-positive VTA neurons compared to CON mice. Extracellular single-unit recording revealed that MCH significantly suppressed the firing rate of OX-A-responsive neurons in the VTA. MCH attenuated the hedonic feeding response induced by OX-A in HFD mice, and administration of MCHR1 antagonist (SNAP94847) significantly potentiated the effect of OX-A. Chemogenetic inhibition of MCH neurons improved the activity of OXR1-expressing neurons, which could be reversed by pretreatment with an OXR1 antagonist (SB334867). Furthermore, chemogenetic inhibition of MCH enhanced hedonic feeding behavior, which was counteracted by SB334867 treatment in HFD mice.ConclusionMelanin-concentrating hormone could attenuate the hedonic feeding behavior induced by orexin-A in the VTA of HFD mice.